2014
DOI: 10.1002/wrna.1270
|View full text |Cite
|
Sign up to set email alerts
|

Ilf3 and NF90 functions in RNA biology

Abstract: Double-stranded RNA-binding proteins (DRBPs) are known to regulate many processes of RNA metabolism due, among others, to the presence of double-stranded RNA (dsRNA)-binding motifs (dsRBMs). Among these DRBPs, Interleukin enhancer-binding factor 3 (Ilf3) and Nuclear Factor 90 (NF90) are two ubiquitous proteins generated by mutually exclusive and alternative splicings of the Ilf3 gene. They share common N-terminal and central sequences but display specific C-terminal regions. They present a large heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 90 publications
(223 reference statements)
4
106
0
Order By: Relevance
“…Nuclear factor 90 (NF90), a major spliced form of interleukin enhancer binding factor 3 (ILF3), was first identified on the basis of its ability to bind to the IL2 promoter in activated T cells [23], and it was subsequently found to bind double-stranded (ds) RNA structural elements [24]. Recent studies have shown that NF90 forms a complex with NF45 and plays multifunctional roles in the cells, including transcription, and microRNA biogenesis [25].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor 90 (NF90), a major spliced form of interleukin enhancer binding factor 3 (ILF3), was first identified on the basis of its ability to bind to the IL2 promoter in activated T cells [23], and it was subsequently found to bind double-stranded (ds) RNA structural elements [24]. Recent studies have shown that NF90 forms a complex with NF45 and plays multifunctional roles in the cells, including transcription, and microRNA biogenesis [25].…”
Section: Introductionmentioning
confidence: 99%
“…1B). [22][23][24] Analyses of these candidate targets in CF cells indicated that CSNK1G2 and IF3/NF90 mRNA levels were comparable in CF and control cells. However, RPTOR mRNA was significantly lower in IB3-1CF cells than in IB3-1/S9 control cells and thus subsequent analyses focused on the role RPTOR in regulating the CF disease phenotype.…”
Section: Identification Of Candidate Targets Of Mir-155 In Cfmentioning
confidence: 99%
“…Using unbiased mass spectrometry to identify mRNA stability factors modified by IL-19, we identified an RBP termed ILF3 (interleukin enhancer binding factor 3) (16). In humans, ILF3 is also known as NF90, NFAR1, and DRBP76 (17). They are all transcribed from the ILF3 gene; although they are used interchangeably, most often they are referred to as ILF3, the gene they are transcribed from.…”
mentioning
confidence: 99%
“…They are all transcribed from the ILF3 gene; although they are used interchangeably, most often they are referred to as ILF3, the gene they are transcribed from. ILF3 is primarily known for its role in innate immunity by participation in cellular antiviral responses (17). ILF3 has been shown to regulate transcription (18)(19)(20), post-transcriptional RNA stabilization (21)(22)(23), nuclear export (17), and translation in response to viral infection (19,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation